The Formulation of Student Social Interaction Model at Halal Tourism Area on Lombok Island - Abral, Waslul (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aims to formulate a model of student social interaction, especially junior high school students at the halal tourism area on the Lombok island. The method used is mixed method with data collection conducted by purposive sampling technique and Analytical Hierarchy Process (AHP). The result and discussion of alternative policy of social interaction development in Lombok island, West Nusa Tenggara province, Indonesia are: (1) Increasing parentrole of student. (2) Strengthening the role of ulama/community leaders. (3) Teachers in stil positive social interaction of students through school and laity programs. (4) The goverment has an important role in facilitating the parents, teachers and ulama/community leaders in developing positive social interaction of students, so that social conflicts that can cause dispute in Lombok society can be avoided.